Validated HPTLC method for the quantitation of levetiracetam in pure and tablet dosage form - T G, likitha; Gnana Babu C., Jose; H G., Sowmya (International Journal of Advanced Chemistry, 2020)
A rapid, simple, precise and accurate high performance thin layer chromatographic method has been developed and validated for the estima-tion of Levetiracetam in bulk and tablet dosage form. The Levetiracetam was chromatographed on silica gel 60 F254 HPTLC plate as a sta-tionary phase. The mobile phase was Ethyl acetate: Methanol: Ammonia in the ratio of 7:1:2 respectively. It gave a dense and compact spot of Levetiracetam with an Rf value of 0.56. The quantitation was carried out at 210 nm. The method was validated in terms of linearity, accu-racy, precision and specificity. The statistical analysis proved that the developed method is accurate and reproducible with linearity in the range of 100 to 500 ng/spot. The limit of detection and limit of quantitation for Levetiracetam were 3.55 and 10.66 ng/spot respectively. The developed method can be employed for the routine analysis of Levetiracetam in the tablet dosage form.